“Bugou?”: História, tecnologia e diversidade, conhecendo Grace Hopper em um minijogo digital - Tanaka, Ellen Ami; Bruschi, Carla Rodrigues; Odakura, Valguima (Anais do Women in Information Technology (WIT); 2025: Anais do XIX Women in Information TechnologyDO - 10.5753/wit.2025.8078, 2025)
The participation of women in computing and STEAM (Science, Technology, Engineering, Arts and Mathematics) remains low, partly due to the historical erasure of their contributions. This article introduces an interactive minigame named “Bugou” about Grace Hopper, a computing pioneer, making her legacy more accessible to young audiences. Through simple and engaging mechanics, the game fosters learning and reflection on diversity in technology, aiming to increase women’s visibility in computing and inspire future generations. The minigame was evaluated using an educational game evaluation model which showed that “Bugou” promotes knowledge about Grace Hopper while being entertaining.